Intracellular Polyphenol Wine Metabolites Oppose Oxidative Stress and Upregulate Nrf2/ARE Pathway - Chiara Stranieri; Flavia Guzzo; Sofia Gambini; Luciano Cominacini; Anna Maria Fratta Pasini (MDPI AG, 2022)
Moderate wine consumption has been associated with several benefits to human health due to its high polyphenol content. In this study, we investigated whether polyphenols contained in a particular red wine, rich in polyphenols, can pass the cell membrane and switch the oxidant/antioxidant balance toward an antioxidant pattern of THP-1 cells and human cardiomyocytes through a gene regulatory system. First, we identified which metabolite polyphenols present in red wine extract cross cell membranes and may be responsible for antioxidant effects. The results showed that the wine metabolites in treated cells belonged mainly to stilbenes, flavan-3-ols derivatives, and flavonoids. Other metabolites present in cells were not typical wine metabolites. Then, we found that red wine extract dose-dependently lowered reactive oxygen species (ROS) induced by tert-butyl hydroperoxide (TBHP) up to 50 ± 7% in both cell lines (p < 0.01). Furthermore, wine extract increased nuclear Nrf2 of about 35 ± 5% in both cell lines (p < 0.01) and counteracted its reduction induced by TBHP (p < 0.01). The rise in Nrf2 was paralleled by the increase in hemeoxygenase-1 and glutamate-cysteine ligase catalytic subunit gene expression (both mRNA and protein) (p < 0.01). These results could help explain the healthful activity of wine polyphenols within cells.